EFFECTS OF LOSARTAN AND METFORMIN ON VASCULAR PROSTANOIDS RELEASE IN RATS IN A HIGH-FAT DIET. (June 2018) - Puyó, A.M.; Lee, H.J.; Cantú, S.M.; Donoso, A.S.; Choi, M.R.; Peredo, H.A.
Abstract : Objective: High-fat diet in rats is an experimental model that resembles human metabolic syndrome (MS). This multifactorial alteration is related to hypertension. Metformin (Mf, antidiabetic drug used in type 2 diabetes and MS treatment); and losartan (L, an angiotensin 1 receptor antagonist) play an important role in the regulation of vascular tone. Prostanoids (PR) are endogenous substances derived from arachidonic acid via cyclooxygenases with vasoactive effects. The aim of this study was to analyze the effects of Mf and L on prostanoids (PR) release by the mesenteric vascular bed (MVB). Design and method: Six groups (n = 6) of male Sprague-Dawley rats were studied during 8 weeks: Control (C), standard diet (SD) and tap water (W) to drink; HF diet (HF), 50% (w/w) bovine fat added to SD and W; C + Mf (CMf), SD + 500 mg/Kg/day Mf in W; C + L (CL), SD + 30 mg/Kg/day L in W; HF + Mf (HFMf) 500 mg/Kg/day Mf in W; HF + L (HFL) 30 mg/Kg/day L in W. MVBs were removed and incubated and the released PR measured by HPLC. Adiposity index is calculated: body weight/MVB weightx100. Results: HF diet increased systolic BP (SBP, mmHg, HF: 145 ± 5 vs. C: 118 ± 2, p < 0.01); MVB adiposity index (%, HF: 1.7 ± 0.1 vs. C: 0.9 ± 0.04, p < 0.01); and the release of vasoconstrictor PR thromboxane (TX) B2, stable metabolite of TXA2, (ng PR/mg of tissue, HF: 117 ± 6 vs. C: 66 ± 2, p < 0.001); and prostaglandin (PG) F2alpha (ng/mg, HF: 153 ± 9 vs C: 88 ± 3, p < 0.001). In HFM and HFL groups, M and L treatment prevented the increases of SBP (HFM: 127 ± 2, HFL: 111 ± 3 vs. HF, p < 0.001 and p < 0.01), TXB2 release (ng PR/mg of tissue, HFM: 65 ± 12, HFL: 66 ± 7 vs. HF, p < 0.05 and p < 0.01); and PGF2alpha (ng PR/mg of tissue, HFM: 99 ± 13, HFL: 90 ± 7 vs. HF, p < 0.01 and p < 0.05). Meanwhile Mf also prevented the increase of MVB adiposity index (%, HFM: 1.3 ± 0.2 vs. HF, p < 0.05). Conclusions: Treatments with Mf and L could exert beneficial effects on the vascular system improving endothelial dysfunction by preventing the increase of vasoconstrictor PR in MVB. In addition, Mf prevents adiposity increase.